Isotopic evidence for distinct sources of mercury in lake waters and sediments - Chen, Jiubin; Hintelmann, Holger; Zheng, Wang; Feng, Xinbin; Cai, Hongming; Wang, Zhuhong; Yuan, Shengliu; Wang, Zhongwei (Chemical geology, 2016)
Lakes are important ecosystems where mercury (Hg) may undergo extensive methylation and bioaccumulation in the aquatic food web. It is thus crucial to understand the sources of Hg in lake systems. Mercury isotope composition is a powerful tracer of its sources in the environment. However, previous studies on Hg isotope compositions in lake systems mainly focus on the aquatic organism and sediments, whereas lake water that provides the nutrients for the bottom of aquatic food chain has received much less attention. Here we report Hg isotope compositions in surface water and sediments of 8 freshwater lakes in Ontario, Canada. We determined significantly positive Δ199Hg and Δ200Hg values in surface water of all lakes, which are similar to previously reported isotope signature of local atmospheric precipitation. In contrast, the isotope compositions of lake sediments show predominantly negative Δ199Hg and negligible Δ200Hg values that are similar to atmospheric elemental Hg(0) and terrestrial soils and plants. We conclude that the source of Hg in lake surface water is likely dominated by direct atmospheric precipitation, while the Hg in lake sediments is primarily derived from watershed inputs of terrestrial particles. The concurrent odd Hg isotope anomalies in surface waters suggest that methylmercury (MeHg) from the watershed wetland, together with Hg(II) derived from the catchment weathering is likely another Hg source to lake waters besides atmospheric deposition. We suggest that the different Hg sources and isotope compositions between lake water and sediments would result in different isotope signatures for MeHg that is produced in water column and in sediments. Therefore, our study not only elucidates the sources of Hg to lake systems, but also has implications in distinguishing between different MeHg sources and in tracing the bioaccumulation of MeHg in aquatic organism. •Occurrence of even mercury isotope anomalies is imprinted onto surface water.•Mercury isotope anomalies establish a direct link of Hg in lake surface waters to atmospheric deposition.•Watershed methylmercury is also an important Hg source in lake waters and food webs.•Lake sediments are isotopically decoupled from the lake waters and the atmosphere.